Uneven Effects of Sleep Apnea on Semicircular Canals and Otolithic Organs - Xu, Xin-Da; Chen, Bin-Jun; Sun, An-Rong; Zhang, Qing; Cheng, Ying; Ren, Dong-Dong; Yu, Jing; Luo, Hui-Ping (Frontiers in Neurology, 2022)
Objective This study aimed to explore how obstructive sleep apnea (OSA) affects the function of each vestibular organ and to identify the correlations among them. Methods A prospective study was conducted involving 32 healthy controls and 64 patients with OSA. The objective detection methods of the utricle and saccule are vestibular-evoked myogenic potentials (VEMPs). A combination of the caloric test and video head impulse test (vHIT) was used to comprehensively evaluate the objective function of semicircular canals. Results Elevated thresholds (p < 0.001), decreased waveform amplitudes (p < 0.001), prolonged first wave latencies (p < 0.001), and shortened first interpeak latencies (p < 0.001) were observed in both ocular VEMP (oVEMP) and cervical VEMP (cVEMP). A significant difference was found in the caloric test comparison (χ2 = 4.030, p = 0.045) but not in the vHIT. The intergroup comparison of normal rates among the VEMPs, caloric test, and vHIT groups showed a significant difference (p < 0.001). Conclusion The impairment of vestibular function in patients with OSA was uneven and biased. More attention should be given to vestibular dysfunction in the diagnosis and treatment of OSA.